An intelligent hybrid interfacing converter of fuel cell powered telecom loads for efficient power conversion. (March 2021) - Muthusamy, Kaleeswari; Muthusamy, Madheswaran; Kaur, Rajvir; Krishnasamy, Vijayakumar
Abstract: This paper is a step towards 'green telecom tower' by eliminating the diesel generator from telecom power supply. The fuel cell based power supply has been proposed for telecom towers in remote and rural areas. The challenge of meeting the prerequisite of telecom power supply which are reliability and regulated DC distribution bus voltage in the environment of fuel cell is addressed by proposing the intelligent hybrid controller. The proposed controller has inherited the best characteristics from linear and non-linear controller. The controller is easy and inexpensive to design and implement as well as has robust response against source side disturbance (fluctuating output voltage of fuel cell) and load side disturbance (varying telecommunication signal traffic). Meta-heuristic algorithms has been implemented to tune the PID based intelligent hybrid controller without the need of extensive mathematical modeling of the complete system. A modified adaptive real-value coded genetic algorithm has been proposed to enhance the performance of the controller which is tested against other algorithms such as genetic algorithm, particle swarm optimization and gray wolf optimization. The extensive analysis and simulation has been carried out to validate the performance of the intelligent hybrid controller for fuel cell based power supply to telecom towers.